RANCANG BANGUN JARINGAN KOMPUTER MENGGUNAKAN CABLE DAN WIRELESS PADA SMKN 1 CIBINONG - Martanto, Markus Lilik; Adianto, Harna; Wahyudi, Endang; Hanif, Aswar (Universitas Multi Data Palembang, 2024)
Abstract Advances and developments in technology are increasingly rapid, both hardware and software, computer technology has been widely used by school agencies, especially computer networks that are often used by schools in every laboratory, especially in the IT department, are LAN networks (Local Area Networks) and WLAN networks. (Wireless Local Area Network), including the TKJ Laboratory of SMKN 1 Cibinong which still uses a local network in each laboratory, therefore the author makes a final project on designing a network Computer system using a cable (Local Area Networks) and adding a wireless network (Wireless Local Area Network) to make it easier to access the internet without having to use a Lan cable. In using the internet network, of course there must be network security, so the authors make wireless network security with hotspot login and create user profiles for students and teachers who teach at the TKJ Laboratory and limit access to websites that are not related to the material in the TKJ department. Keywords: Computer network system, Wireless, Hotspot Login